Five-Year Trends in Low-Density Lipoprotein Cholesterol Management in a Primary Healthcare Centre in Kaunas - Gediminas Urbonas; Lolita Šileikienė; Leonas Valius; Evelina Grigalė; Vilius Kaupas; Tautvydas Juška; Gabrielė Vėbraitė; Ingrida Grabauskytė (Medicina)
Background and Objectives: Low-density lipoprotein cholesterol (LDL-C) is a marker of cardiovascular risk and its management. This study evaluated LDL-C control trends in patients treated at a primary healthcare center in Lithuania. Materials and Methods: Five-year (2019–2023) data on patients aged 40 years or older diagnosed with dyslipidemia were extracted from a real-world data and analytics platform, TriNetX. Patients were grouped into three groups: patients with dyslipidemia only (control group), patients with dyslipidemia and diabetes, and patients with dyslipidemia and cardiovascular disease (CVD). The following LDL-C goals were used for analysis: <1.4 mmol/L (a goal for very-high-risk patients in primary or secondary prevention), <1.8 mmol/L (a goal for high-risk patients), and <3.0 mmol/L (a goal for low-risk patients). Results: There were 18,646 patients with dyslipidemia. Of them, 8.9% of patients had diabetes, and 3.1% of patients had CVD. The median LDL-C concentration was significantly lower in patients with diabetes (2.82 mmol/L, p < 0.05) and in patients with CVD (2.45 mmol/L, p < 0.05) than in the control group (3.35 mmol/L). A trend of decreasing median LDL-C over the years was observed in all groups, with the lowest median values in 2023. The proportion of patients with LDL-C levels < 3 mmol/L increased from 32.0% in 2019 to 41.5% in 2023. The proportion of diabetic patients achieving LDL-C < 1.8 mmol/L increased from 7.4% to 25.9%, and those achieving LDL-C < 1.4 mmol/L increased from 3.1% to 10.6%. The proportion of patients with CVD achieving LDL-C < 1.8 mmol/L increased from 14.2% to 36.6%, and those achieving LDL-C < 1.4 mmol/L increased from 3.0% to 14.0%. Conclusions: Trends in the control of LDL-C levels are positive over 5 years, but a significant proportion of patients still did not reach the recommended target levels.